Post-exertional symptoms distinguish Myalgic Encephalomyelitis/Chronic Fatigue Syndrome subjects from healthy controls. - Mateo, Lariel J.; Chu, Lily; Stevens, Staci; Stevens, Jared; Snell, Christopher R.; Davenport, Todd; VanNess, J. Mark; Mooney, Amy (Work, 2020)
BACKGROUND: Post-exertional malaise (PEM) is an exacerbation of symptoms that leads to a reduction in functionality. Recognition of PEM is important for the diagnosis and treatment of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). OBJECTIVE: Symptoms following cardiopulmonary exercise testing were compared between ME/CFS patients and healthy controls. METHODS: Open-ended questionnaires were provided to subjects following two maximal exercise tests, 24 hours apart. Subjects evaluated how they felt at five time points. Responses were classified into 19 symptom categories. RESULTS: ME/CFS subjects (n = 49) reported an average of 14±7 symptoms compared to 4±3 by controls (n = 10). During the seven days afterwards, ME/CFS subjects reported 4±3 symptoms. None were reported by controls. Fatigue, cognitive dysfunction, and sleep problems were reported with the greatest frequency. ME/CFS patients reported more symptom categories at higher frequencies than controls. The largest differences were observed in cognitive dysfunction, decrease in function, and positive feelings. CONCLUSIONS: A standardized exertional stimulus produced prolonged, diverse symptoms in ME/CFS subjects. This provides clues to the underlying pathophysiology of ME/CFS, leading to improved diagnosis and treatment.